RELIGIOUS TOLERANCE AND POLITICAL STABILITY (A CASE STUDY OF KAZAKHSTAN AND RUSSIA) - TSEPKOVA, Irina (CENTRAL ASIA AND THE CAUCASUS, 2010)
Religious tolerance is a very sensitive sphere and a highly complicated social phenomenon, the limits of which are very hard to outline. It embraces moral and religious consciousness, hardly controlled by external means, and forms of behavior, including those regulated by law. The subjects of these forms of consciousness and behavior belong to various social levels—individual (micro level), confessional groups (macro level), and the state (mega level). In view of the highly complicated structures of the subjects of religious tolerance/intolerance, religious policy should take into account the difference between the “external” (secular) and the “internal” (confessional) interpretation of religious tolerance: each of them raises highly specific questions—related to internal tolerance (relations between religions) and external tolerance (state policy in the sphere of religion or the freedom of conscience). In other words, the “internal” interpretation of religious tolerance is suggested by the dogmas, while the “external” interpretation by the state laws. Tolerance of people of confessions other than one’s own; attitude toward atheism, interpretation of the role and place of religion in the life of society and each of its members, assessment of the trends of secularism and sacralization and of religious fundamentalism, interpretation of the religion/science correlation, and acceptance of religious pluralism can be described as indicators of religious tolerance. Pluralism of religious confessions, denominations, alliances, and organizations which can be described as the hallmark of our day and age has moved religious tolerance to the frontline of social and political stability and the emerging civil society.